Science Teachers’ Perceptions on Continuing Professional Development (CPD), Self-Efficacy, and Instructional Performance (American Journal of Multidisciplinary Research and Innovation, 2024)
This study examined science teachers’ perceptions of Continuing Professional Development (CPD) and its impact on their self-efficacy and instructional performance. It investigated the types of CPD activities attended, perceptions of CPD, the relationship among perceptions, self-efficacy, and instructional performance, and the challenges faced in attending CPD activities. The study involved 71 Junior high school science teachers from major schools in ten districts in Baguio City, selected through purposive sampling. Data were collected using checklists, a survey-checklist, a self-assessment instrument, and an open-ended questionnaire. Findings showed that teachers mainly attended conferences, seminars, and workshops for CPD, while advising dissertation and thesis candidates was the least attended. CPD positively influenced self-efficacy in classroom management, instructional strategies, and student engagement. Most teachers strongly agreed that they could teach proficiently according to objectives. Significant correlations were found between self-efficacy and perceptions of CPD in instructional strategies and classroom management, but not in student engagement. Positive correlations were observed between self-efficacy and instructional performance in all areas. Meanwhile, major challenges faced by educators in their pursuit of advancement undertakings included financial constraints, work-related conflicts, and limited availability of authorized CPD providers.